Discourse, power and resistance in Nadine Gordimer’s Occasion for Loving: a foucaultian reading - Seyed Mohammad Marandi; Ramin, Zohreh; Shabanirad, Ensieh (Penerbit Universiti Kebangsaan Malaysia, 2017)
This paper is concerned with two fundamental phenomena in any society: discourse and power. It focuses on how power is being reproduced by discourse in society. Many forms of social inequality, such as those based on gender, class, sexuality and race, are construed, perpetuated and legitimated by discourse. The critical method in this study is influenced by Michel Foucault’s theories on power and discourse. It is in discourse, as Foucault puts it, that power and knowledge are joined together. However, Foucault argues that discourse is both the means of oppressing and the means of resistance. This study examines these forms of the discursive reproduction of power in Nadine Gordimer’s novel, Occasion for Loving (1963). The researchers aim to explore how the control and power shaping and defining discourse in the prison-society of apartheid South Africa reveals the inevitable entanglement of the personal and the political and how such a relationship can be used by the artist to resist and subvert the controlling social and political discourses. The paper also sheds light on how Gordimer generates a discourse that challenges the apartheid’s legal discourse on race and interracial sexuality.